Evolução da Distribuição dos Financiamentos do PRONAF entre as Unidades da Federação, no Período de 1999 a 2009 - de Souza, Paulo Marcelo (2011)
The objective of this study is to analyze the distribution of the Proanf resources between the Federation Units, during the last decade. The results show that, initially, the distribution of these resources became less concentrated. However, this trend changed at the end of the period, and, currently, the Pronaf resources remains concentrated in a few states, mainly Rio Grande do Sul, Santa Catarina, Paraná and Minas Gerais. It was also observed that the distribution of the resources does not reflect, completely, the distribution of familiar agriculture between the states. These resources have been directed, mainly, to states whose participation in the value produced by familiar agriculture is high.